Glucocorticoid induced osteoporosis in neurological patients: prevention and treatment - K. V. Antonova; N. A. Suponeva; N. I. Shcherbakova; D. A. Grishina; N. V. Belova; L. V. Kononova (Нервно-мышечные болезни)
Glucocorticoids (GCs) are often prescribed for neurologic patients. Autoimmune diseases of central and peripheral nervous system, neuromuscular disorders are associated with disability and life-threatening complications, and require long-term high-dosage administration of GCs. GC-therapy is a crucial decision to be made by a neurologist in collaboration with a patient, and requires strict observance of clear guidelines on the prevention, diagnosis and treatment of possible complications. One of the most frequent complications of GCs is osteoporosis. According to the Russian and international guidelines, all the patients must undergo preliminary and follow-up laboratory and instrumental examination, as well as administration of calcium and vitamin D during the whole period of GC-therapy. In case of a high fracture risk or if osteoporosis is diagnosed, antiresorptive therapy is indicated.